30th Anniversary of Diplomatic Relations Between Russia and South Africa - SKUBKO Yury Sergeevich (Ученые записки Института Африки Российской академии наук)
On March 14, 2022 the Institute for African Studies of the Russian Academy of Sciences held a round table discussion to mark the 30th anniversary of the establishment of diplomatic relations between the Russian Federation and the Republic of South Africa, organized by the Centre for Southern African studies. The history and current state of relations between the two countries and peoples were discussed by African studies researchers, Russian Foreign ministry officials and diplomats in South Africa, South African public figures and civil society activists, veterans of the national liberation movement. Among issues discussed were historic ties between Russia and South Africa dating back to the 18th century, first diplomatic contacts in the 19th century, participation of Russian volunteers in the Anglo-Boer war of 1899–1902, Russian emigration to South Africa, Soviet aid to the national liberation struggle against the apartheid regime, particularly relations with the ANC, first Soviet-South African diplomatic ties, influence on them of perestroika and the dissolution of USSR. Current problems of cooperation and development of relations in different fields within strategic partnership between the two countries, particularly, within the framework of BRICS, were also discussed.